2021
DOI: 10.1021/acs.jpca.1c02817
|View full text |Cite
|
Sign up to set email alerts
|

Role of Size and Composition on the Design of Superalkalis

Abstract: Superalkalis and superhalogens are atomic clusters that mimic the chemistry of alkali and halogen atoms, respectively; the ionization energies of the superalkalis are less than those of alkali atoms, while the electron affinities of superhalogens are larger than those of the halogen atoms. These superions can serve as the building blocks of a new class of supersalts with applications in solar cells, metal-ion batteries, multiferroic materials, and so on. While considerable progress has been made in the design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… (A) Geometric structures of NM 4 (M = Li, Na, and K) clusters reproduced from Zhang and Chen (2019) ; (B) charge density difference in (A) Li 3 B 6 H 6 , (B) Li 3 B 6 F 6 , and (C) Li 3 B 6 (CN) 6 clusters reproduced from Banjade et al (2021) . (C) Charge density difference in (A) Li 3 B 12 H 12 , (B) Li 3 B 12 F 12 , and (C) Li 3 B 12 (CN) 12 clusters ( Banjade et al, 2021 ); (D) superalkali cation Li 3 + with water molecules, Li 3 + (H 2 O) n ( n = 1–5), reproduced from Hou et al (2018) with permission from the Royal Society of Chemistry; (E) a small series of hydroxides (XM n+1 OH) where (XM n+1 ): superalkali; M (K and Na): alkali metal atom; n, maximal formal valence of the central atom X (F, O, and N), and n ≥ 1. …”
Section: Structural and Electronic Features Of Superalkali-based Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“… (A) Geometric structures of NM 4 (M = Li, Na, and K) clusters reproduced from Zhang and Chen (2019) ; (B) charge density difference in (A) Li 3 B 6 H 6 , (B) Li 3 B 6 F 6 , and (C) Li 3 B 6 (CN) 6 clusters reproduced from Banjade et al (2021) . (C) Charge density difference in (A) Li 3 B 12 H 12 , (B) Li 3 B 12 F 12 , and (C) Li 3 B 12 (CN) 12 clusters ( Banjade et al, 2021 ); (D) superalkali cation Li 3 + with water molecules, Li 3 + (H 2 O) n ( n = 1–5), reproduced from Hou et al (2018) with permission from the Royal Society of Chemistry; (E) a small series of hydroxides (XM n+1 OH) where (XM n+1 ): superalkali; M (K and Na): alkali metal atom; n, maximal formal valence of the central atom X (F, O, and N), and n ≥ 1. …”
Section: Structural and Electronic Features Of Superalkali-based Speciesmentioning
confidence: 99%
“…With the combination of superalkalis having low IPs and superhalogens having high EA, super-ions may be used as construction blocks of a novel series of supersalts having uses in multiferroic materials, metal-ion batteries, solar cells, and so on. Jena et al thoroughly described the role of size and composition in the design of supersalts consisting of two dissimilar classes of clusters belonging to the closo -borane family, Li m B n X n ( m = 1–3; n = 6, 12; X = H, F, and CN) and Zintl ion family, Li m Be@Ge 9 , in the framework of the density functional theory (DFT) with hybrid exchange-correlation functional (ωB97xd) as well as Gaussian basis sets [6-311+G (d, p)] ( Banjade et al, 2021 ). In this work, the stabilities of such a composition of clusters were regulated by the Wade–Mingos polyhedral skeleton electron pair theory (i.e., shell closure rule), and additionally, the jellium shell closure rule was deployed to understand the stability of the Be@Ge 9 cluster.…”
Section: Structural and Electronic Features Of Superalkali-based Speciesmentioning
confidence: 99%
“…In addition, Liu et al [29] devised alkaline-earth metal based pseudoalkali or superalkali cations. Various other superalkali systems such as zintl, [30,31] organometallic, [32,33] organic [34,35] etc., were designed and characterized in the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Metal clusters, which consist of several to hundreds of atoms, have received great attention in both the fundamental science and potential applications in catalysis, energy, environment, and materials. It is generally believed that the diverse properties and functionalities of metal clusters come from their adjustable size, composition, shape, and quantum confinement effect. , In the cluster science, it is worth highlighting that many researchers recently demonstrated that the superatom is a series of special clusters, which possess the potential of mimicking the chemistry of individual atoms, and they further proposed that a three-dimensional (3D) periodic table can be constructed by fitting the superatoms into the third dimension. …”
Section: Introductionmentioning
confidence: 99%